Parkinson’s Disease in a Dish: What Patient Specific-Reprogrammed Somatic Cells Can Tell Us about Parkinson’s Disease, If Anything? - J. Drouin-Ouellet; R. A. Barker (Stem Cells International)
Technologies allowing for the derivation of patient-specific neurons from somatic cells are emerging as powerful in vitro tools to investigate the intrinsic cellular pathological behaviours of the diseases that affect these patients. While the use of patient-derived neurons to model Parkinson’s disease (PD) has only just begun, these approaches have allowed us to begin investigating disease pathogenesis in a unique way. In this paper, we discuss the advances made in the field of cellular reprogramming to model PD and discuss the pros and cons associated with the use of such cells.